Mental health and social connectivity: The positive role of neighborhood interaction for international students in Japan - Day, Robert; Nakamura, Keiko; Tashiro, Yuri (Journal of International Students, 2025)
The Japanese government has set a goal to increase the number of inbound international students by 2033. International students’ mental health is affected by various environmental stressors, including ‘living space’ which is an important but understudied element. We conducted a cross-sectional study in the Greater Tokyo area of Japan to determine the association between living space characteristics and mental health status. Data was collected from 177 international students, who were mostly postgraduate (95%) and from Asia (72%), and 40% exhibited symptoms of moderate psychological distress (GHQ-12≥14pts). A multivariable Poisson regression analysis revealed that absence of ‘socialization opportunities with nearby residents’ was associated with increased prevalence of moderate psychological distress, though notably the association was only observable for those students who had lived in Japan for more than one year (PR 1.79, p